COVID‐19 and Headache: A Primer for Trainees - Bobker, Sarah M. (Headache, 2020)
OBJECTIVE: To summarize for the trainee audience the possible mechanisms of headache in patients with COVID‐19 as well as to outline the impact of the pandemic on patients with headache disorders and headache medicine in clinical practice. BACKGROUND: COVID‐19 is a global pandemic caused by the novel coronavirus severe acute respiratory syndrome coronavirus 2, of which a large subset of patients features neurological symptoms, commonly headache. The virus is highly contagious and is, therefore, changing clinical practice by forcing limitations on in‐person visits and procedural treatments, more quickly shifting toward the widespread adaptation of telemedicine services. DESIGN/RESULTS: We review what is currently known about the pathophysiology of COVID‐19 and how it relates to possible mechanisms of headache, including indirect, potential direct, and secondary causes. Alternative options for the treatment of patients with headache disorders and the use of telemedicine are also explored. CONCLUSIONS: Limited information exists regarding the mechanisms and timing of headache in patients with COVID‐19, though causes relate to plausible direct viral invasion of the nervous system as well as the cytokine release syndrome. Though headache care in the COVID‐19 era requires alterations, the improved preventive treatment options now available and evidence for feasibility and safety of telemedicine well positions clinicians to take care of such patients, especially in the COVID‐19 epicenter of New York City.